Analisis Korelasi Kelas Orang Tua (Parenting) dengan Perkembangan Sosial Emosional Anak di Lembaga PAUD Mumtaz - Alviana Alviana; Suharyani Suharyani; Muhammad Arief Rizka; Herlina Herlina (Jurnal Paedagogy, 2022)
This study aims to analyze the correlation between parenting class and the socio-emotional development of children in PAUD Mumtaz, East Lombok Regency. This research method uses a correlational method with a quantitative approach. The research sample was 56 people. The research instrument used a questionnaire, documentation, and observation. The data analysis technique uses statistical analysis with the product moment correlation formula. Based on the results of the analysis of the value of rcount (product moment) obtained in this study is 0.22, while the value of rcount in the table with a significance level of 5% and N = 56 is 0.22, or (0.22<0.26), the data This indicates that the rcount value obtained in this study is smaller than the table rcount value. So it can be concluded that there is no correlation between parenting class and children's social and emotional development at PAUD Mumtaz.